Diversidade de leveduras associadas a flores e frutos de murici (Byrsonima crassifolia, L. Kunth) - Andréa Ohanna Santos Carvalho (2017)
Plants have many different microhabitats favorable to the growth of yeasts, such as flowers, fruits, sap and decomposing tissues. However, most yeasts that colonize these microenvironments depends on insects toward dispersal. Thus, flowers and fruits visited by insects usually contains heavy yeast population, wich makes them, including insects, excellent substrates for the isolation of new species of these microrganisms. In this context, little is known about the pattern of yeast diversity associated with flowers, fruits and insects that visit the murici (Byrsonima crassifolia) in cerrado ecosystem. The flowers of this species does not produce nectar, and this plant offers oil and pollen as floral resources to attract pollinators. The present study aims to evaluate the diversity of yeasts associated with flowers, fruits and insects visitors muricizeiro. In this case, strains yeasts are going isolated from flowers samples, fruits, and associated with murici collected in the city of Araguatins, state of Tocantins. The yeasts were identified by morphological characterization, PCR firgerprinting and sequencing domains D1/D2 of the large subunit ribosomal RNA gene, as well as sequencing the internal transcribed regions (ITS1-5.8S-ITS2) of the ribosomal RNA gene. To diversity analysis, is going to performed α and β diversity analysis. The sampling effort is going to assessed using accumulation curves. From the collected samples were isolated 500 yeasts belonging to 94 species, of which 20 could be considered as new species. The results showed that the community of yeasts present in the flowers, fruits and insects associated to B. crassifolia is composed mostly of species commonly recovered from plant samples. Among the flower samples, the most frequent yeasts species were Aureobasidium pullulans, Papiliotrema flavescens, Candida apicola and Meyerozyma guillermondii. The most frequent species in the insect samples was Moniliella fonsecae, followed by A. pullulans. In the fruit samples, the most frequent species were Pichia occidentalis, Zygosccharomyces bailii, Sterigmatomyces halophilus, P. kluyveri, P. kudriavzevii and C. tropicalis. The diversity analyzes showed that the yeast community found in the insect samples was the most diverse. The accumulation curves of the yeast species did not reach stability, indicating that a larger sampling effort could cover the species richness expected in the studied substrates.